Glycomyces terrestris sp. nov., isolated from extremely arid soil from Yuanmou Earth Forest. Issue 1 (30th January 2021) - Li, Qinyuan; Li, Guiding; Lang, Lei; An, Defeng; Jiang, Chenglin; Jiang, Yi
Abstract : A Gram-stain-positive, mycelium-forming actinobacterium, YIM 121974 T was isolated from an extreme arid soil sample collected at Yuanmou Earth Forest, Yunnan Province, PR China. Classification using a polyphasic approach suggested that strain YIM 121974 T belonged to the genus Glycomyces and was closely related to Glycomyces dulcitolivorans SJ-25 T (98.3 %), Glycomyces scopariae YIM 56256 T (98 %), Glycomyces mayteni YIM 61331 T (97.9 %), Glycomyces albidus NEAU-7082 T (97.9 %), Glycomyces sambucus CGMCC 4.3147 T (97.7 %), Glycomyces artemisiae IXS4 T (97.6 %) and Glycomyces parisis CPCC 204357 T (97.5 %), but could be distinguished from its closest relatives by a combination of phenotypic and phylogenetic features. Average nucleotide identity values of YIM 121974 T to its closest phylogenetic neighbours were 70.7–88.9 %, which are lower than the threshold of 95 %. The digital DNA–DNA hybridization values between YIM 121974 T and these relative species were 18.0–36.3 %, which are also well below the cut-off value (>70 %) for species delineation. The DNA G+C content of strain YIM 121974 T was 72.3 mol% (draft genome sequence). The predominant menaquinone was MK-11. The phospholipids were composed of diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol, phosphatidylinositol mannoside, phosphoglycolipid and glycolipid. The major fatty acid compositions were iso-C16 : 0, anteiso-C15 : 0 and anteiso-C17 : 0 . The draft genome of isolate YIM 121974 T was found to contain 11 secondary metabolite biosynthesis gene clusters by using the antiSMASH server. Based on the above observations, strain YIM 121974 T could be distinguished from closely related species belonging to the genus Glycomyces . Thus, strain YIM 121974 T represents a novel species of the genus Glycomyces, for which the name Glycomyces terrestris sp. nov. is proposed. The type strain is YIM 121974 T (=KCTC 39870 T =DSM 106742 T ).